Differences in Student Learning Outcomes Between Before and After Using Video Media Tutorials on Research Statistics Through E-Learning - Depi Pramika; Nuryanti Permata Sari (Journal of World Conference (JWC), 2021)
The purpose of this study was to determine the differences in student learning outcomes between before and after the use of research statistics tutorial videos through e-learning. The method used in this research is a comparative method with a quantitative approach. Data analysis techniques used documentation and tests. Data analysis used the IBM SPSS 24 application. The results showed that there were significant differences in student learning outcomes between before and after the use of statistical research video tutorials through e-learning both descriptively and by hypothesis testing. So it is recommended that the instructors use video tutorials as a medium to help the learning process.